1987
DOI: 10.1038/jcbfm.1987.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cerebroprotective Agents on Cerebral Blood Flow and on Postischemic Energy Metabolism in the Rat Brain

Abstract: Summary: Male Wi star rats were subjected to forebrain ischemia of lO min duration by clamping both common carotid arteries and simultaneously lowering systemic blood pressure to 40 mm Hg by exsanguination. Re covery was achieved by removing the arterial clamps and reinfusing the blood. Cortical levels of high-energy phos phates and glycolytic substrates were determined enzy matically. Naftidrofuryl (10 or 20 mg/kg i.p.) or ketamine (5 mg/kg i.v.) were applied 30 min prior to the induction of ischemia. S(-)-Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…and emopamil are in accordance with earlier observations [Bielenberg ct al., 1987a;Krieglstein and Weber, 1986;Weber and Krieglstein, 1985], The re sults are further confirmed by observations that emopamil and nimodipinc accelerate the restoration of high-energy phosphates in the artificially ventilated rat following 10 min of ischemia [Bielcnberg ct al., 1987b]. The increased level of glucose-6-phosphate following emopamil administra tion is also consistent with earlier findings in the isolated perfused rat brain [Bielenberg et al, 1987a], This effect has been documented as well in the artificially ventilated rat for emopamil and nimodipinc [Bielenberg et al. 1987b],…”
Section: Discussionsupporting
confidence: 79%
“…and emopamil are in accordance with earlier observations [Bielenberg ct al., 1987a;Krieglstein and Weber, 1986;Weber and Krieglstein, 1985], The re sults are further confirmed by observations that emopamil and nimodipinc accelerate the restoration of high-energy phosphates in the artificially ventilated rat following 10 min of ischemia [Bielcnberg ct al., 1987b]. The increased level of glucose-6-phosphate following emopamil administra tion is also consistent with earlier findings in the isolated perfused rat brain [Bielenberg et al, 1987a], This effect has been documented as well in the artificially ventilated rat for emopamil and nimodipinc [Bielenberg et al. 1987b],…”
Section: Discussionsupporting
confidence: 79%
“…In accord with these results, Bielenberg et al [12] described increased postischemic creatine phos phate and ATP levels in rat brains in vivo caused by 10 mg/kg i.p. naftidrofuryl, whereas a higher dose (20 mg/kg i.p.)…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, it seemed to be of some significance whether naftidrofuryl could change the LCBF during the early postischemic period. In addition, it has already been shown that naftidrofuryl elevated the cortical ATP level 2 min after ischemia probably because of its blood flow increasing activity in cortical tissue [ 12], Further more, we found a postischemic increase in LCBF of rat cortical tissue caused by calcium antagonists only 2 min after ischemia in the same experimental model [13,14], Thus, it seemed to be advisable to determine LCBF in this study 2 and 10 min after ischemia. As the present results of the LCBF measurements elucidate, the post ischemic blood flow is not generally enhanced by nafti drofuryl.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1718 Like many other calcium channel blockers, (S)-emopamil is a potent cerebral vasodilator, capable of increasing cortical blood flow by 50% or more 19 . 20 without affecting local cerebral glucose utilization.…”
Section: Relationship Of Mean±sem Cortical Infarct Volume To Time Of mentioning
confidence: 99%